PENGGUNAAN MEDIA GAMBAR SEBAGAI UPAYA PENINGKATAN PENCAPAIAN KRITERIA KETUNTASAN MINIMAL (KKM) BAHASA INDONESIA SISWA KELAS I SDN 4 KURANJI - SRIMULYANIMARGANINGSIH, CLIMENTIA (Universitas Mahasaraswati Mataram, 2018)
This study aims to analyze the improvement of the achievement of Indonesian KKM by optimizing the use of visual media in First Class Students Semester 1 SDN 4 Kuranji Lesson Year 2017/2018. This study is a classroom action research using students as many as 28 people as the subject of research. Data obtained through observation during the learning process, group assignments and the results of discussion, and test results of student learning given at the end of the cycle. Data analysis uses descriptive qualitative and quantitative in the form of average and percentage improvement of mastery learning result.The result of the analysis shows that the optimization of the use of visual media is able to increase the achievement of Indonesian KKM of First Class Students Semester 1 SDN Negeri 4 Kuranji in each cycle. From the result of student learning test in cycle I obtaines result that the achievement of student's learning mastery reach 72%, and in cycle II increased to 92%.